Visuality and socio-political communication in Nigeria's banknote portraits. - Morgan, Trevor Vermont (Visual Studies, 2022)
In this article, I examine portraits in Nigeria's banknotes offering an interpretive analysis of their significance with the purpose of espousing on existing knowledge. I believe the reading and interpretation of these portraits would provide a good communication and understanding of their socio-political and nationalistic properties. Located at the interface between visuality and society this paper discursively examines the repertoire of 10 portraits of Nigeria's 'nationalists'. My reading is based on nationalism, historiography, and iconology. The socio-political reflection in these portraits offers relevant clues to the current developments in Nigeria. Beyond being just images on the economic tool of money, the portraits act as indicators of Nigeria's socio-political formation and historical trajectory. Understanding this might help to improve politics and society in a multi-ethnic country like Nigeria.